Pengaruh Mendengarkan Podcast berbahasa Inggris terhadap Skor TOEFL pada pengikut akun Collegemenfess - Mansyur, Nurhalizah; Hermansyah, Sam; H. Syamsu T (Global Synthesis in Education Journal, 2023)
This study was conducted to determine the teacher's perception of the use of the Contextual Teaching and Learning (CTL) method in teaching English. This research was conducted at SMP Negeri 4 Panca Rijang. This research used descriptive qualitative method. The participants are 3 English teachers who teach grades 1, 2, and 3 at SMP Negeri 4 Panca Rijang. The instruments of this research are interviews and questionnaires. The results showed 3 positive perceptions and 3 negative perceptions. As for 3 of the negative perception. Based on the data obtained, the researchers concluded that the results of interviews and questionnaires, positive perceptions where all teachers said that Contextual Teaching and Learning learning was very helpful for teachers in delivering learning material and helping students  more easily understand the material presented in the learning process.